The use of nuclear weapons under review: Is their use legal in situations of armed conflict? - Enrico Headrington, Alessandra (2021)
The discussion regarding nuclear weapons uses or tests in the context of an armed conflict, and the subsequent consequences that have already been noticed in the attacks on Hiroshima and Nagasaki, poses several humanitarian challenges in relation to the tragic personal, environmental, and material costs for those who do not take part in the hostilities: the civilian population. Therefore, it become important to conduct an assessment to develop its illegality under international law but specifically under International Humanitarian Law.To that extent, it is possible to analyze its use in contexts where the legality of the use of force is examined (ius ad bellum), as well as in situations of armed conflict (ius in bello). This latter view is fully discussed in the present article. Thus, the legal consequences in the light of International Humanitarian Law and specific treaties on the matter are thoroughly developed. This includes the step-by-step assessment of three key principles: distinction, proportionality, and military necessity, which allow to objectively elucidate whether the use of nuclear weapons may or may not be lawful during the conduction of hostilities.In summary, the answer to its legality is negative. The use or tests of nuclear weapons and the trend towards the non-proliferation, disarmament, and more lately its complete prohibition is unquestionable from a legal approach. Additionally, its contravention not only becomes a serious violation of International Humanitarian Law but could eventually lead to the determination of individual criminal responsibility, for those who order and/or execute attacks with prohibited weapons whose effects are indiscriminate, as nuclear weapons are.